Trypanotolerant livestock in the context of trypanosomiasis intervention strategies - Agyemang, Kwaku (FAO, 2004)
Trypanosomiasis poses a considerable constraint on livestock-agricultural development in tsetse-infested areas of sub-Saharan Africa. Many efforts to limit or eradicate trypanosomiasis have failed or have had limited success. However, in certain areas of West Africa, livestock production remains possible, despite the presence of tsetse fly, through the use of cattle and small ruminant breeds that are tolerant to the disease. This paper provides an overview of the problem and the various options for its control. Emphasis is placed on the definition of the role of trypanotolerant livestock as an integrated approach to control the disease.